Geographic information systems and big data analytics: optimizing digital adoption to develop tourism in Buton Islands, Indonesia - Lawelai, Herman; Sadat, Anwar; Suherman, Ansar; Alfinta, Muhammat Alim; Ishaq, L.M. Ahsan (Department of Government Studies Universitas Muhammadiyah Makassar, 2024)
This research aims to optimize tourism potential in the Buton Islands, Indonesia, using Geographic Information Systems (GIS) and Big Data Analytics. The study addresses the low tourism potential in the region and constraints in tourism development, such as lack of information and data. Qualitative methods include document analysis, literature studies, and focus group discussions. Quantitative methods involve surveying respondents about the use of GIS and Big Data Analytics in tourism development. Data was collected from government documents, online news, and direct observation of tourist sites. The results emphasize the importance of IT and GIS in developing the tourism sector in the Buton Islands, particularly in Baubau City and South Buton Regency. GIS is crucial for identifying and managing tourism potential, while Big Data Analytics helps optimize development by analyzing visitation trends, tourist preferences, and consumer behavior patterns. The integration of these technologies can improve tourist experience and efficiency of tourism-related public services. By integrating GIS, Big Data Analytics, and Information Technology, local government and stakeholders can collaborate to create a superior tourism experience, support local economic growth, and ensure the sustainability of the natural and cultural environment in the Buton Islands.